2005
DOI: 10.2114/jpa.24.321
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Color Temperature of Illumination on Physiological Functions

Abstract: This article presents our recent studies on the effects of color temperature on the taste sense and the influence of color temperature on bright light

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 7 publications
2
17
0
1
Order By: Relevance
“…This result showed that the 180-s production time intervals feel faster-passing in the red light condition than in the other color conditions. Katsuura et al (2005) found the same result that the subjective time sense runs faster in the red light condition than in the blue light condition. However, an interesting finding in the present study was that this effect was attenuated in the 600-s time estimation task, because the time sense in the red light condition came to show a marginally significant difference from the other color conditions.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…This result showed that the 180-s production time intervals feel faster-passing in the red light condition than in the other color conditions. Katsuura et al (2005) found the same result that the subjective time sense runs faster in the red light condition than in the blue light condition. However, an interesting finding in the present study was that this effect was attenuated in the 600-s time estimation task, because the time sense in the red light condition came to show a marginally significant difference from the other color conditions.…”
Section: Discussionsupporting
confidence: 52%
“…Light can elicit acute physiological and psychological responses in human beings. The magnitude of responses depends on the color temperatures, intensity, wavelength components and duration of light exposure (Noguchi and Sakaguchi, 1999;Katsuura et al, 2005). Recent studies have found an effect of the light wavelength on suppression and phase delay of the melatonin rhythm (Morita and Tokura, 1998;Brainard et al, 2001;Lockley et al, 2003Lockley et al, , 2006Hanifin et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Mental tasks generally consist mainly of vigilance, short-term memory, and tracking. In the case of the complex task established by Jin et al (2003) using a combination of visual search and short-term memory, many physiological indicators including the electroencephalogram, HRV, and blood pressure, which were often used in other studies, such as those conducted by Katsuura et al (2005), Jin et al (2003), and Aasman et al (1987), exhibited significant change in response to level of difficulty. Because driving a car and operating machinery always require visual search and recording and reproduction of short-term memory, they were considered optimal tasks for the present study.…”
Section: Taskmentioning
confidence: 99%
“…Electroencephalography (EEG) is an electrophysiological method to record the brain activity and its change according to different lighting conditions. 12 Because prior EEG studies were limited to investigations for young subjective, [13][14][15] little is known about neurophysiological characteristics of the lighting effects in elderly subjects. Therefore, herein, we investigated brain oscillatory characteristics according to brightness and color temperature of light by analyzing power spectral density and functional connectivity derived from resting-state EEG recordings.…”
Section: Introductionmentioning
confidence: 99%